DEMNITATEA UMANĂ ȘI LIBERTATEA RELIGIOASĂ ȘI DE CONȘTIINȚĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Dignity and Freedom of Religion and ConscienceFrom the Universal Declaration of Human Rights and the European Convention on Human Rights and Biomedicine, until the Final Act signed in Helsinki, international organisations and conventions affirm their commitment to defend and sustain human dignity. Themantica of the article includes topical issues and theoretical and practical interest, with the value of a moral factor with implications in several existential areas. The first part of the article includes notions, defining the term, its irportance and the place of human dignity in relation to other human freedoms. An approach to the origins will help us in analyzing the relationship between dignity and freedom of religion and conscience. It is known that both the Church, the state, the right exists as far as people believe in them. This reality applies without the retention and relationship between human dignity and the right to freedom. So we are trying to reaffirming human rights as preconditions for every human being to live with dignity. The conclusion that emerges from the relationship between human dignity and freedom of religion and conscience reaffirms the value of human dignity as a foundation of freedom of religion and conscience in the current context.